Isolation, characterization and cytotoxic activity of arborinine from glycosmis pentaphylla (Retz.) DC. on human mammary gland adenocarcinoma (MCF7) cell line - Mohd Hussain, Nurlaili Najmi; Uzir, Bisha Fathamah; Mohd Hassan, Norazian (2015)
Arborinine is an acridone alkaloid found exclusively in Rutacae family has showed cytotoxic potency against various cancer cell lines. The aims of this study were to isolate and identify arborinine from local G. pentapylla (Retz. D) and to determine its cytotoxicity activity on human mammary gland adenocarcinoma, MCF 7 cell line. The leaves of G. pentaphylla which were collected from Kelantan, Malaysia were air-dried and extracted with chloroform followed by acid-base extraction. Wet column chromatographic separation was employed to furnish arborinine. The structure of arborinine was elucidated by comparing its spectroscopic data to that of published reports. The cytotoxic effect of arborinine was investigated by means of the MTT assays, using human cell lines MCF7. The result showed that 0.1295 g (12.15%) of yellow needle-like crystals or arborinine was yielded from 4.4168 g of crude alkaloidal extract. Arborinine inhibit 50% of the MCF7 cells growth at 6.25±0.02uM after 72 hour of treatment and morphological changes were observed after 24, 48 and 72 hour incubation. The data presented suggest that arborinine can be regarded as an excellent starting structure for potential development of new anticancer agent.